Paleobiodiversity in the Darriwilian (Middle Ordovician) of the Naturtejo UNESCO Global Geopark (Portugal) - Sofia Pereira; Jorge Colmenar; Cristiana Esteves; Ícaro Dias da Silva; Miguel Pires; Carlos Neto de Carvalho (Geoconservation Research)
Middle Ordovician successions occur at Naturtejo UNESCO Global Geopark in five Variscan-folded, kilometer- to tens of kilometer-long structures. Four of them revealed to be fossiliferous in the different recognized lithostratigraphic units, middle-to-uppermost Darriwilian in age, with particular emphasis for Brejo Fundeiro (Oretanian regional chronostratigraphic stage) and Fonte da Horta (Dobrotivian regional stage) formations. Recent paleontological and biostratigraphic works have detected most of the previously recorded and new fossil sites, improving the Middle Ordovician biostratigraphy of this region and updating the knowledge of its fossil assemblages, which are fairly more diverse than previously considered. The good preservation of the fossils and their relevance to understanding the climax of the Global Ordovician Diversification Event at high paleolatitude shallow marine environments, as well as the protection or identification of some of the fossil sites as UNESCO Geopark’ geosites, make certain their interpretation and use in already existing geotrails and new interpretation centers and school programs.